Students’ Perception on Code Switching Used by English Lecturer - Fitriyah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This research is a continuation of research that conducted previously with the title "An Analysis of Code Switching Used by English Lecturer" which focuses on types of code-switching and the purpose of code-switching used by the lecturer. Previous research showed that the functions that appeared most often were attracting students' attention, social functions and the last is organize learning and teaching activities effectively. Based on these findings, the author is interested in conducting further research from a different perspective. The researchers are interested in conducting further research from students’ perspective. The researchers would like to analyse and prove that code-switching carried out by lecturers is indeed needed by students and is effective in the teaching and learning activities. This research is a descriptive qualitative research. The data are considered as descriptive qualitative because they are form of written and spoken (words) rather than numbers. The research design used in this research is survey research design, meanwhile the researchers collected the data (sample) during English class that conducted by the researchers. The findings of this study, several practical recommendations can be proposed to enhance the effectiveness of code switching in teaching contexts in higher education. Conduct regular training sessions for lecturers to enhance their understanding of teaching strategies that integrate code switching. Lecturers need a deep understanding of how to implement code switching effectively and responsively to students' needs. Further research is also needed to delve into the long- term effects of code switching on academic achievement and students' language proficiency. Thus, this approach not only enriches students' learning experiences but also supports the inclusive and multicultural vision of modern higher education institutions.